Inter-individual variability in peripheral oxygen saturation and repeated sprint performance in hypoxia: an observational study of highly-trained subjects - Takei, Naoya; Muraki, Ryuji; Girard, Olivier; Hatta, Hideo (Frontiers in Sports and Active Living, 2024)
Individual variations in peripheral oxygen saturation (SpO2) during repeated sprints in hypoxia and their impact on exercise performance remain unclear despite fixed external hypoxic stimuli (inspired oxygen fraction: FiO2). This study examined SpO2 individual variations during repeated sprints in hypoxia and their impact on exercise performance. Thirteen highly-trained sprint runners performed 10 × 10-s cycle sprints with 30-s passive recoveries in normobaric hypoxia (FiO2: 0.150). Mean power output (MPO), post-sprint SpO2, and heart rate for each sprint were assessed. Sprint decrement score (Sdec), evaluating fatigue development, was calculated using MPO variables. Participants were categorized into a high saturation group (HiSat, n = 7) or a low saturation group (LowSat, n = 6) based on their mean post-sprint SpO2 (measured 10–15 s after each sprint). Individual mean post-sprint SpO2 ranged from 91.6% to 82.2%. Mean post-sprint SpO2 was significantly higher (P < 0.001, d = 1.54) in HiSat (89.1% ± 1.5%) than LowSat (84.7% ± 1.6%). A significantly larger decrease in Sdec (P = 0.008, d = 1.68) occurred in LowSat (−22.3% ± 2.3%) compared to HiSat (−17.9% ± 2.5%). MPO (P = 0.342 d = 0.55) and heart rate (P = 0.225 d = 0.67) did not differ between groups. There was a significant correlation (r = 0.61; P = 0.028) between SpO2 and Sdec. In highly-trained sprint runners, individual responses to hypoxia varied widely and significantly affected repeated sprint ability, with greater decreases in SpO2 associated with larger performance alterations (i.e., larger decrease in Sdec).